Pakistan's trade performance and potential with ASEAN region: Recent trends and future opportunities. Issue 1 (17th August 2020) - Kamal, Muhammad Abdul; Shad, Sakeena; Khan, Saleem; Ullah, Assad; Khan, Khalid
Abstract : Owing to declining export growth and escalating trade deficits in Pakistan, this study investigates the dynamics of comparative advantage, complementarity, and pinpoints potential export products in the ASEAN region. This study scrutinizes the trade dynamics between Pakistan and ASEAN over the period 2003–2016 by extracting International Trade Centre (ITC), trade map data. The analyses are based on the Trade intensity index, the Revealed comparative advantage index, Trade complementarity index, and trade potential method. The results show that Pakistan has the highest comparative advantage over ASEAN in chapters 03, 08, 41, 61, 62, and 63 at HS‐2 digit product‐level data. With Malaysia and Philippines, Pakistan's trade complementarity is stronger than Indonesia, Singapore, Thailand, and Vietnam. The outcomes also suggest that there is a huge trade potential that exists between Pakistan and ASEAN member countries. These findings are useful for policy consideration in identifying product specialization for enhancing competitiveness and promoting economic growth.